(untitled) (Annals of Medical Research, 2022)
Aim: The purpose of this study was to evaluate brain-derived neurotrophic factor (BDNF) and cortisol levels in patients with bruxism. Relationships between clinical variables (myofacial pain, dental anxiety and masticatory function) and BDNF and cortisol levels were also investigated. Materials and Methods: In this prospective study, patients were divided into 4 groups according to the severity of bruxism; group I (no bruxism, control group), group II (mild bruxism), group III (moderate bruxism), group IV (severe bruxism). Cortisol and BDNF levels were evaluated from venous blood samples of patients. Myofacial pain was evaluated with the Visual Analogue Scale (VAS), dental anxiety was evaluated with the Modified Dental Anxiety Scale (MDAS), and masticatory function limitation was evaluated with the Jaw Functional Limitation Scale (JFLS). Results: The study conducted with 75 patients (15 in group I, 20 in group II, 20 in group III, and 20 in group IV) aged 18-64 years. BDNF and cortisol levels increased as the severity of bruxism increased. The cortisol level of group III was significantly higher than that of group I (p=0.008). BDNF and cortisol levels in group IV were significantly higher than group I (p=0.043, p=0.006). VAS, JFLS and MDAS values increased as the severity of bruxism increased. VAS pain scores correlated significantly with BDNF and cortisol levels (r=0.220, p=0.038; r=0.286, p=0.013). MDAS and JFLS values were significantly correlated with cortisol levels (r=0.279, p=0.015; r=0.271, p=0.19). Conclusion: Plasma BDNF and cortisol levels can contribute to the assessment of bruxism severity and its clinical findings such as myofacial pain, masticatory efficiency and dental anxiety.